2015
DOI: 10.1152/jn.00278.2015
|View full text |Cite
|
Sign up to set email alerts
|

Decision making: effects of methylphenidate on temporal discounting in nonhuman primates

Abstract: Decisions are often made based on which option will result in the largest reward. When given a choice between a smaller but immediate reward and a larger delayed reward, however, humans and animals often choose the smaller, an effect known as temporal discounting. Dopamine (DA) neurotransmission is central to reward processing and encodes delayed reward value. Impulsivity, the tendency to act without forethought, is associated with excessive discounting of rewards, which has been documented in patients with at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 75 publications
5
16
0
Order By: Relevance
“…Consistent with the literature [9][10][11][12][13][14] , therapeutic effects on impulsive choices were observed at the low dose. Notably, the MPH effect depended on the animals' initial impulsive state 49,50 .…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with the literature [9][10][11][12][13][14] , therapeutic effects on impulsive choices were observed at the low dose. Notably, the MPH effect depended on the animals' initial impulsive state 49,50 .…”
Section: Discussionsupporting
confidence: 89%
“…Our results are consistent with findings in many pharmacological studies that increasing dopamine levels leads to more patient choices, whereas decreasing dopamine levels leads to decreases in choice of delayed rewards or willingness to exert effort for larger rewards (Kayser et al, 2012;Salamone & Correa, 2012;Floresco, Tse, & Ghods-Sharifi, 2008;Bizot et al, 2007;Salamone, Correa, Farrar, & Mingote, 2007;van Gaalen, van Koten, Schoffelmeer, & Vanderschuren, 2006;Pietras, Cherek, Lane, Tcheremissine, & Steinberg, 2003;de Wit, Enggasser, & Richards, 2002;Cardinal, Robbins, & Everitt, 2000;Wade, de Wit, & Richards, 2000;Richards, Sabol, & de Wit, 1999). In particular, a recent study showed that administration of methylphenidate, which increases extracellular levels of dopamine in the BG and pFC, decreased temporal discounting in nonhuman primates (Rajala, Jenison, & Populin, 2015). However, other studies have found that increases in dopamine lead to decreases in patient choices (Pine et al, 2010;Evenden & Ryan, 1996;Logue et al, 1992) or to no differences (Acheson & de Wit, 2008;Hamidovic, Kang, & de Wit, 2008).…”
Section: Dopamine and Consideration Of Future Eventssupporting
confidence: 91%
“…One study [69] proposes that different sub-populations with ADHD exist, with distinguishable symptoms, cognitive and physiological profiles, which are caused by deficits in either the modulation of cortical control centers or reward circuits. Recent studies in nonhuman primates 1) identified the orbitofrontal cortex as a region that processes reward but not working memory-related information [70], 2) demonstrated reward signals integrate with action signals in at least one region of the prefrontal cortex (dorsal anterior cingulate cortex) [71] and 3) showed that administration of methylphenidate affected the temporal discounting of rewards [72]. …”
Section: Neural Mechanisms Of Other Cognitive Domains Associated Withmentioning
confidence: 99%